Paraovarian cyst as the cause of uterine prolapse - Čančar, Vladimir; Ivanović, Radenko; Lalović, Nenad; Milinković, Biljana; Sladoje, Dragana (Archive of Oncology, 2020)
Paraovarian cysts originate from the mesothelium and are presumed to be remnants of Müllerian or Wolffian ducts. In majority of cases they are found to be 10-80 mm in diameter and do not cause any symptoms. Paraovarian cysts can be found unexpectedly during an operation or on ultrasound examination performed for other reasons. They are most freequently discovered on ultrasound examination. However, due to the proximity of the ovary for which cystic formations are not rare, the diagnosis of these lesions can be a challenge. They are mostly asymptomatic and only large lesions (≤20 cm in diameter) become symptomatic. Although these are mostly benign tumors, in rare cases they can become borderline or true malignancies. Most paraovarian cysts are found in the third and fourth decade of life. Paraovarian cyst complications include: compression of the surrounding structures of the pelvis minor and abdomen, pelvic pain, cyst torsion and rupture. Except for the already mensioned complications available literature has so far failed to show cases of uterine prolapse caused by an increase of intra-abdominal pressure due to the expansive growth of giant paraovarian cystic formation.